RELATIONSHIP OF KINESTETIC CAPABILITY AND EMOTIONAL INTELLIGENCE WITH THE ACCORDANCE OF THE WOODBALL GATTING - Khadiq, Muhamad (JOURNAL SPORTINDO, 2022)
Relationship between Kinesthetic Ability and Emotional Intelligence with the Accuracy of the Gatting Woodball Punch . Department of Sport Coaching Education, Faculty of Sports Science, Semarang State University